Efficacy and safety of leadless pacemaker implantation in octogenarians: a single-center experience - Zhang, Zhipeng; Wu, Zonglei; Luan, Chao; Dai, Shiyu; Chen, FeiFei; Gao, Yuchen; Huang, Fenglan; Sun, Yuanjun; Yin, Xiaomeng; Gao, Lianjun; Liu, Jinqiu; Yu, Xiaohong (Frontiers in Cardiovascular Medicine, 2025)
AimsLong-term complications occur in approximately 4%–12% of patients with standard transvenous pacemakers (TVPs), most of whom are elderly. The leadless pacemaker (LP) has emerged as an effective alternative to traditional TVPs, offering a lower complication profile. However, data on LP implantation in octogenarians remain limited, and concerns persist regarding its feasibility and safety in this population. This study aimed to assess the feasibility and clinical outcomes of LP implantation in octogenarians.Methods and ResultsBetween January 2021 and January 2024, 154 patients (mean age 75.5 ± 9.8 years) who underwent LP implantation at our center were consecutively included. The study cohort was stratified into two age groups: octogenarians (≥80 years, mean age 84.2 ± 3.3 years, n = 66) and non-octogenarians (<80 years, mean age 69.0 ± 7.9 years, n = 88). Outcomes assessed included electrical parameters, procedural characteristics, and complication rates at hospital discharge and throughout the follow-up period. The procedure was successfully performed in all patients. Six patients (five octogenarians and one non-octogenarian) underwent LP implantation along with concurrent removal of transvenous pacing systems due to prior pocket infections. No device-related infections were observed. LP implantation combined with atrioventricular node ablation (AVNA) was successfully performed in three octogenarians without any complications. Despite having a higher burden of comorbidities, as indicated by a higher age-adjusted Charlson Comorbidity Index (7 IQR 5–8 vs. 4 IQR 3–6, p < 0.001),the octogenarian group demonstrated comparable outcomes to the non-octogenarians. No statistically significant differences were observed between the groups regarding electrical parameters, procedure duration, fluoroscopy time during a median follow-up of 12 (IQR 6–22) months. The proportion of patients requiring more than two deployment attempts was significantly higher among octogenarians (48.5% vs. 26.1%, p = 0.032). These findings suggest that LP implantation is safe and effective in octogenarians when performed at experienced centers. However, the incidence of significant periprocedural complications was relatively higher in octogenarians than in non-octogenarians (4.5% vs. 1.1%), although this difference was not statistically significant.ConclusionsLP implantation appears to be a safe and effective therapeutic option for octogenarians, including those with more combabilities. Therefore, it should be considered a viable alternative to conventional TVPs in this aging population.